Phytochemicals Levels and Antioxidant Capacities of Figs Flowers Fruits - Mohammed, Messaoudi; Maroua, Merah (Nepal Journal of Biotechnology, 2020)
Since antiquity, phenolic compounds produced by plants were known as free radical scavengers and as powerful antioxidants. Huge interest has been made by researchers to the traditional uses of medicinal plants against illnesses related to oxidative stress. This study measures the correlation that can be existed between the antioxidant capacity and phytochemical s levels of four varieties of Ficus carica fruits, figs flowers or "Bakor" as called locally in Algeria. Therefore, extracts were assessed for determining their antioxidative potentials using both test of total antioxidant capacity and DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging test followed by quantitative phytochemical analysis to estimate the total flavonoid level (TFL), the total phenolic level (TPL), the total anthocyanin level (TAL) and the condensed tannins level of plants methanolic extracts. A positive correlation was observed between phenolics content and the antioxidant capacity of figs flowers methanol extracts. The methanolic extract of Bechar (MeOH Var.2) chelated 87,9± 1,23 % of the DPPH free radical with IC50 value equal to 0,185 mg/g DW. A high antioxidant ability of almost all extracts is, probably, related to the appreciable rates of flavonoids, phenolics and tannins showed by those fig extracts. The highest value of phenolics level was detected among the variety 1 methanolic extract of Bechar (MeOH Var.1) of 10,4 mg GAE/g DW.